Safety of low-volume PEG-asc bowel cleansing preparation for colonoscopy: identifying patients at risk for hypokalemia in a prospective cohort study - Reumkens, Ankie; Bakker, Christine Minke; van Kraaij, Sebastiaan J.W.; Winkens, Bjorn; Raijmakers, Maarten T.; van Nunen, Annick B.; van Deursen, Cees Th.B.M.; Masclee, Ad A.M. (Endoscopy International Open, 2021)
Background and study aims The aim of bowel cleansing preparation should be high-quality results and conformance with safety standards. Previously, we reported that hypokalemia occurred in 23.6 % of patients after bowel preparation in a high-risk population on diuretics or hospitalized and referred for colonoscopy. Here we report on a prospective study in a non-selected colonoscopy cohort to identify patients at risk of developing hypokalemia before and after bowel cleansing with low-volume polyethylene glycol with ascorbic acid (PEG-asc).Patients and methods From January 1 to July 31, 2016, we included all patients undergoing colonoscopy in our institution. Prevalences of hypokalemia before and after PEG-asc bowel cleansing for colonoscopy were calculated and risk factors for developing hypokalemia after PEG-asc bowel cleansing were identified.Results In total, 2011 patients were included in the analysis. Of these, 0.8 % had hypokalemia before bowel cleansing with PEG-asc. After bowel preparation, 5.4 % developed hypokalemia. Of the patients, 281 were considered to have “high cardiac risk.” The combination of “high cardiac risk” and hypokalemia was present in 1 % of the initial colonoscopy population. Female sex, colorectal cancer diagnosis, and thiazide use were found to be significant predictors for hypokalemia after use of PEG-asc. No arrhythmias or serious adverse events due to hypokalemia occurred.Conclusions Physicians referring patients for colonoscopy should be aware that “high cardiac risk” patients and those on thiazide diuretics undergoing bowel cleansing for colonoscopy are a risk of developing post-cleansing hypokalemia but it remains to be determined whether their risk of developing life-threatening arrhythmias is truly increased.